A 30-per-cent deviation is too wide - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2010)
Following Prime Minister Lee's recent announcement that the Electoral Boundaries Review Committee (EBRC) had been convened, SMU Assistant Professor Eugene Tan opined that the 30-per-cent deviation rule, of which the EBRC operates on, is too wide and ?overly-generous? in small and compact Singapore. Professor Tan also commented that the committee's redrawing of electoral boundaries should avoid being seen as gerrymandering.